Menata Ruang Hijau di Tengah Kawasasan Industri Gerakan Penghijauan Desa Kareo Melalui Program BIVIT - Rudianto Rudianto; Siti Aulia Nurmedina; Ahmad Rizky Widodo; Maryati Maryati; Nadya Septiani; M. Raffa Al Ghifran; Anisa dwi Paramita (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Desa Kareo, Serang Regency, faces environmental challenges due to the dominance of industrial activities, resulting in a lack of green spaces and increased air temperatures. This situation prompted the implementation of a greening program as a form of community service to support the improvement of the village's environmental quality. The program was carried out using a participatory approach, involving residents in identifying critical land areas, planting seedlings (BIVIT), and post-planting maintenance. Greening efforts focused on open lands, roadside areas, and public facilities that were previously barren. The results showed an improvement in the visual comfort of the environment, a reduction in barren areas, and increased community participation in preserving the plants. These findings confirm that locally collaborative greening initiatives have significant potential to restore environmental quality, especially in areas heavily impacted by industrial activities. Reforestation efforts focused on previously barren open spaces, roadsides, and public facilities. These previously unproductive lands now serve as green spaces that provide ecological benefits, such as carbon sequestration and improved air quality. Furthermore, tree planting has a positive impact on lowering local temperatures, a crucial issue given the increasing temperature levels associated with urbanization and industrial activity. The reforestation program demonstrated significant improvements in environmental visual comfort, a reduction in barren areas, and increased community participation in caring for the planted plants. The community members involved in the program demonstrated a sense of ownership of their environment and a commitment to maintaining the sustainability of the planted plants. These findings confirm that reforestation initiatives involving local collaboration have significant potential to restore environmental quality, particularly in areas impacted by industrial activity. With this program, it is hoped that the quality of life of the Kareo Village community will improve as the ecological balance in the area is maintained.